Is School a Better Environment than Home for Digital Game-Based Learning? The Case of GraphoGame - Ronimus, Miia; Lyytinen, Heikki (Human Technology, 2015)
This study investigated how the use of an online reading game differs in home and school environments. First and second graders (N = 194) participated in an 8-week training during which they used the reading program GraphoGame either at home or at school under the supervision of parents or teachers. Child participants were recommended by parents and teachers recruited from the list of GraphoGame users, and adults decided whether the training took place at home or at school. We measured the frequency and duration of playing, children's engagement, development of reading skill and reading interest, and adult supportive involvement. The results revealed that children who played GraphoGame at school showed higher engagement and used it more frequently than players at home. Although teachers were more involved in the children's playing than were parents, only parental involvement was significantly associated with a child's engagement during training and the child's learning outcomes.